Ageing and mobility in Germany: are women taking the fast lane? - Dominika Kalinowska; Uwe Kunert (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Results from travel demand research in many countries show that - on average - women are less mobile and have different mobility patterns than men. Recent longitudinal studies of gender specific travel demand reveal converging mobility of males and females. Moreover, in some countries results show convergence between cohort and gender specific travel demand: women and men display more and more similar travel behaviour while older individuals today have higher mobility demands than ever before. Do these developments hold also for Germany? Based on socio-economic and demographic analysis of gender specific travel behaviour using the German mobility survey data from 2002, we ask what individual travel patterns can be expected for the future in the year 2025. We place emphasis on the importance of educational attainment and labour force participation for the assessment of future personal mobility.
Keywords: R41; J11; J14; J16; 330; Travel demand; cohort effects; gender; households; ageing population; Verkehrsverhalten; Mobilität; Verkehrsprognose; Geschlecht; Privater Haushalt; Alternde Bevölkerung; Frauen; Deutschland